2009
DOI: 10.1088/0031-8949/2009/t138/014013
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of diamond surfaces with fusion relevant plasmas

Abstract: The outstanding thermal properties of diamond and its low reactivity towards hydrogen may make it an attractive plasma-facing material for fusion and calls for a proper evaluation of its behaviour under exposure to fusion-relevant plasma conditions. Micro and nanocrystalline diamond layers, deposited on Mo and Si substrates by hot filament chemical vapour deposition (CVD), have been exposed both in tokamaks and in linear plasma devices to measure the erosion rate of diamond and study the modification of the su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
24
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 18 publications
2
24
0
Order By: Relevance
“…In previous experiments on Pilot-PSI the nano-crystalline and microcrystalline diamond CVD films were exposed to high flux hydrogen plasma: electron density ne = 2×10 19 m −3 , electron temperature Te = 0.31.4 eV (giving energy below 10 eV), ion flux of 2×10 23 m −2 s −1 . CH emission produced by erosion of diamond films was found to be reduced by a factor 2 compared to graphite if Te was less than 1 eV [3]; unfortunately, Tsurf could not be measured at that time. Partial amorphization of the diamond structure within the penetration depth of ions (appearance of sp 2 carbon in XPS) occurred at Te = 1.5 eV [3].…”
Section: Chemical Sputtering Of Carbon and Diamondmentioning
confidence: 94%
See 3 more Smart Citations
“…In previous experiments on Pilot-PSI the nano-crystalline and microcrystalline diamond CVD films were exposed to high flux hydrogen plasma: electron density ne = 2×10 19 m −3 , electron temperature Te = 0.31.4 eV (giving energy below 10 eV), ion flux of 2×10 23 m −2 s −1 . CH emission produced by erosion of diamond films was found to be reduced by a factor 2 compared to graphite if Te was less than 1 eV [3]; unfortunately, Tsurf could not be measured at that time. Partial amorphization of the diamond structure within the penetration depth of ions (appearance of sp 2 carbon in XPS) occurred at Te = 1.5 eV [3].…”
Section: Chemical Sputtering Of Carbon and Diamondmentioning
confidence: 94%
“…CH emission produced by erosion of diamond films was found to be reduced by a factor 2 compared to graphite if Te was less than 1 eV [3]; unfortunately, Tsurf could not be measured at that time. Partial amorphization of the diamond structure within the penetration depth of ions (appearance of sp 2 carbon in XPS) occurred at Te = 1.5 eV [3]. When dealing with higher ion energy, above ~10 eV, more studies devoted to erosion of diamond and defect creation on diamond can be found.…”
Section: Chemical Sputtering Of Carbon and Diamondmentioning
confidence: 94%
See 2 more Smart Citations
“…Diamond has excellent thermal properties and its etching rate by thermal hydrogen is 2 orders of magnitude smaller than that of graphite [10]. Preliminary experiments with diamond coatings deposited by chemical vapour deposition (CVD) on molybdenum substrates have confirmed the lower erosion rate of diamond (factor 3-5) and the good resistance of the material to fusion-relevant conditions [11,12]. Micrometrethick coatings are of limited relevance to a fusion reactor however.…”
mentioning
confidence: 99%